Gadolinium chromite type GdCrO3 nickel-based catalyst for hydrogen production by acetic acid reforming
The construction of a nickel-based catalyst supported by gadolinium chromite-type GdCrO3 was solved by the sol-gel method, which solved the problem of existing catalysts being easily sintered, oxidized and carbon deposited in the acetic acid autothermal reforming reaction, and achieved efficient, stable and high yield hydrogen production of the catalyst.
Patent Information
- Application Number
- CN202510073026.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
Existing nickel-based catalysts are prone to sintering, oxidation and carbon accumulation in acetic acid autothermal reforming reaction, resulting in reduced activity and catalyst deactivation.
The nickel-based catalyst supported by gadolinium chromite type GdCrO3 was constructed by the sol-gel method, and Ni-Gd-Cr-O was used as the active center to form a stable mesoporous structure to improve the thermal stability and resistance to carbon deposits of the catalyst.
The thermal stability, resistance to carbon deposits and sintering ability of the catalyst in the acetic acid autothermal reforming reaction is improved, and the hydrogen yield and catalyst activity and selectivity are significantly improved.
Smart Images

Figure CN119819315A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an application of a gadolinium chromite type GdCrO3 nickel-based catalyst in hydrogen production by autothermal reforming of acetic acid, belonging to the field of hydrogen production by autothermal reforming of acetic acid. Background Art
[0002] Currently, the main way to produce hydrogen is to convert fossil fuels and their derivatives, which has led to an increase in carbon emissions. In contrast, the separation of acetic acid from biomass oil obtained by rapid pyrolysis of biomass and the production of hydrogen using acetic acid as a raw material is a rich and renewable way to produce hydrogen.
[0003] Catalytic reforming of acetic acid is an effective method for producing hydrogen, which mainly includes steam reforming (SR), partial oxidation (POX) and autothermal reforming (ATR). SR is a typical endothermic reaction that requires an external heat source to maintain its progress; while POX is an exothermic process, but the higher oxygen content in the feed gas often leads to a lower hydrogen yield; in contrast, ATR combines the advantages of steam reforming and partial oxidation. By introducing O2 and water into the reaction system at the same time, it can achieve a balance of reaction heat by adjusting the ratio of oxygen to reactants.
[0004] In the process of hydrogen production by autothermal reforming of acetic acid, nickel-based catalysts show high initial activity for the activation of CC, CH and OH in acetic acid as oxygen-containing compounds; however, the introduction of oxygen forms an oxidizing atmosphere at the front end of the catalyst bed, which can reach a local high temperature of 1000°C, which can easily cause sintering of the catalyst carrier, blockage of the pores and agglomeration and sintering of the active components, and also easily cause the active component Ni to be oxidized and deactivated; at the same time, after acetic acid is adsorbed and activated at the active center, it undergoes a series of processes such as dehydrogenation, dehydroxylation, decarboxylation (CH3COOH*→CH3COO*→CH3CO*→CH2CO*→CH2*→CH*) and ketolysis reaction (CH3CO*+CH3*→CH3COCH3), and a large amount of intermediate species such as CH3CO*, CHx* (x=1-3), and C* are generated during the reaction process, which further condense to form carbon deposits and cover the active sites of the nickel-based catalyst, reducing the active sites for the conversion of reactant molecules, reducing the reaction activity or even deactivating it.
[0005] In view of the sintering, oxidation and carbon deposition problems of the above nickel-based catalysts in the process of acetic acid autothermal reforming, the present invention creatively constructs a gadolinium chromite-type GdCrO3-loaded nickel-based catalyst through a sol-gel method, which is applied to the process of acetic acid autothermal reforming hydrogen production. The present invention constructs a gadolinium chromite structure GdCrO3 with lattice constants abc of 5.523, 7.602, and 5.315, respectively, which belongs to the Pnma space group, where Gd 3+ With 8 O 2-Atomic bonding, the distribution range of the Gd-O bond distance is 2.27 - 2.67 Å; while for Cr 3+ binds to 6 O 2- atoms to form a shared-corner CrO6 octahedron, and the distribution range of the Cr-O bond distance is 1.98 - 2.00 Å; among them, there are two unequal O 2- sites. In the first O 2- site, O 2- coordinates with 3 equivalent Gd 3+ and 2 equivalent Cr 3+ atoms. In the second O 2- site, O 2- binds to two equivalent Gd 3+ and two equivalent Cr 3+ atoms to form a distorted shared-corner OGd2Cr2 tetrahedron.
[0006] By calculating the ionic radii of Gd 3+ and Cr 3+ in the gadolinium chromite GdCrO3 constructed in the present invention, the tolerance factor t = 0.79 is obtained, indicating the stable existence of the gadolinium chromite GdCrO3 structure (when 0.75 < t < 1, the structure exists stably). Therefore, a reaction interface with Ni-Gd-Cr-O as the active center can be stably formed; in contrast, the tolerance factor t range of the cubic perovskite structure is 0.95 < t < 1.04, indicating that the structure undergoes lattice distortion on the basis of the cubic perovskite-like structure, thereby increasing the concentration of non-intrinsic oxygen vacancies and making the structure a fast ion conductor with high application potential.
[0007] The innovation of the catalyst of the present invention in the catalytic reaction pathway and structure improves the thermal stability, anti-coking, and anti-sintering capabilities of the catalyst in the autothermal reforming reaction of acetic acid. The results of the activity test of the catalyst applied to the autothermal reforming reaction of acetic acid also show that the catalyst of the present invention has excellent activity, selectivity, and stability. Summary of the Invention
[0008] The technical problem to be solved by the present invention is to provide a new type of catalyst with stable activity, anti-coking, and anti-sintering properties, aiming at the problems of low activity, poor stability, easy coking, and easy sintering of the existing catalyst in the autothermal reforming reaction of acetic acid, which leads to catalyst deactivation. The present invention uses nickel as the active component, introduces gadolinium and chromium components, and creates a gadolinium chromite-type catalyst by the sol-gel method; when the catalyst of the present invention is used in the hydrogen production reaction by autothermal reforming of acetic acid, at a reaction temperature of 700 °C, the acetic acid conversion rate is close to 100%, and the hydrogen yield can be stably maintained at about 2.61 mol-H2 / mol-HAc; the results of the activity test and phase analysis of the catalyst confirm that the catalyst has the characteristics of anti-coking, sintering resistance, and stable structure and activity.
[0009] Technical solution of the present invention:
[0010] The present invention aims at the characteristics of acetic acid autothermal reforming and prepares a nickel-based catalyst supported by a gadolinium chromite type GdCrO3 carrier by a sol-gel method. The chemical composition of the catalyst of the present invention is (NiO) a (GdO 1.5 ) b (CrO 1.5 ) c , wherein a is 0.77-0.89, b is 1.13-1.40, and c is 1.12-1.57; the composition according to the weight percentage of oxides is: nickel oxide is 11.0%-15.5%, gadolinium oxide is 54.3%-65.9%, and chromium oxide is 21.7%-32.2%; the weight percentage of the preferred typical catalyst CDUT-NGC is: nickel oxide is 15.0%, gadolinium oxide is 59.9%, and chromium oxide is 25.1%.
[0011] The specific preparation method steps are as follows:
[0012] 1) According to the proportion of each component in the catalyst (NiO) a (GdO 1.5 ) b (CrO 1.5 ) c , wherein a is 0.77-0.89, b is 1.13-1.40, and c is 1.12-1.57, nickel nitrate, gadolinium nitrate, and chromium nitrate are dissolved in deionized water to prepare a mixed solution #1;
[0013] 2) Prepare a mixed solution of citric acid and ethylene glycol #2 at a total molar ratio of citric acid:ethylene glycol:metal nitrate of 1:1:1; mix solution #1 and solution #2 and stir, keep heating in a water bath at 70°C, continue stirring until gel appears, move the gel into an oven at 105°C for 12 hours, and allow the sample to foam and expand;
[0014] 3) The sample obtained in step 2) was crushed and placed in a tube furnace for calcination. The temperature was raised from room temperature to 600-800°C at a heating rate of 10°C / min and the calcination was maintained for 4 hours. The typical crystal structure is shown in the attached figure. Figure 1 As shown in the XRD spectrum, a crystalline structure of NiO supported on a gadolinium chromite-type GdCrO3 oxide is formed, and a Ni-Gd-Cr-O active center is formed, thereby obtaining the gadolinium chromite-type nickel-based catalyst Ni / GdCrO3 of the present invention; the formed mesoporous structure is as shown in the attached Figure 2 As shown;
[0015] 4) Before use, the catalyst is reduced at a temperature of 600-800°C in a H2 flow at a flow rate of 30 mL / min for 1 h, then purged with nitrogen, and a mixed gas with a molar ratio of acetic acid / water / oxygen = 1 / (1.3-5.0) / (0.21-0.35) is introduced through the catalyst bed to perform an autothermal reforming reaction at a reaction temperature of 600-800°C, normal pressure, and a space velocity of 20000-60000 mL / (g-catalyst·h).
[0016] Beneficial effects of the present invention:
[0017] 1) In view of the characteristics of the acetic acid autothermal reforming process, the present invention adopts a sol-gel method to construct a gadolinium chromite structure GdCrO3 with lattice constants abc of 5.523, 7.602, and 5.315, which belongs to the Pnma space group; in this structure, ① GdCrO3 belongs to the orthorhombic system, in which Gd 3+ With 8 O 2- Atoms combine, and Cr 3+ With 6 O 2- The atoms combine to form a CrO6 octahedron with shared corners; in which there are two unequal O 2- site, in the first O 2- In the site, O 2- With 5 coordination and 3 equal Gd 3+ and 2 equal Cr 3+ Combined, the second O 2- Site with two equivalent Gd 3+ and two equivalent Cr 3+ Atoms combine to form twisted OGd2Cr2 tetrahedrons with shared angles; ② In the gadolinium chromite GdCrO3 constructed by the present invention, Gd 3+ and Cr 3+The ionic radius gives a tolerance factor t = 0.79, proving the stable existence of the gadolinium chromite GdCrO3 structure, providing a stable reaction interface for the acetic acid autothermal reforming reaction process, restricting the migration of metallic Ni, and effectively reducing the aggregation of Ni particles; ③ In addition, the electronegativity of the Gd species in this structure is 1.2, which is relatively small compared to the electronegativity of the Cr species (χ = 1.66). Its outer electron cloud is relatively easy to give electrons, showing a certain electron-donating ability; when the Gd species is introduced, the electrons of Gd shift towards the vicinity of Cr, increasing the electron cloud density around Cr and reducing the electron deficiency degree of Cr, which can effectively balance the electron distribution in the Ni / GdCrO3 catalyst with the gadolinium chromite structure, thereby improving the Lweis acid sites generated by the introduction of Cr species, increasing the basicity concentration, which is conducive to the adsorption and activation of acidic gas CO2 and CH3COOH molecules (CO2 → O* + CO*, CH3COOH → CH3COOH* → CH3COO*), and is conducive to improving the conversion of intermediate products such as CH3COO*, CH3CO*, CH2CO*, CH2* (CH3COO* → CH3CO* + O*, CH3CO* → CH3* + CO*), promoting the forward movement of the water-gas shift reaction (CO + H2O → CO2 + H2), and thus increasing the hydrogen yield.
[0018] 2) The gadolinium chromite type GdCrO3 structure constructed in the present invention has a tolerance factor of 0.79, which is much smaller than the tolerance factor t (0.95 < t < 1.04) of the cubic perovskite structure, indicating that the structure of the present invention has significant lattice distortion compared to the cubic perovskite structure, thereby increasing the concentration of non-intrinsic oxygen vacancies (Ov) and promoting the formation of active sites Gd-Ov-Cr on the interface; ① The formation of these oxygen vacancy defects is conducive to the migration of lattice oxygen in the structure to the surface, improving the oxygen migration rate, and further promoting the adsorption and activation of acetic acid, H2O and O2 molecules (CH3COOH → CH3COOH*, H2O → OH* + H*, O2 → 2O*). The formation of active oxygen species can timely oxidize and gasify the carbon-containing intermediates CHx* (x = 1 - 3) generated during the reaction process and the coke C* formed by the condensation of carbon-containing intermediates into CO / CO2 (C* + O* → CO / CO2), timely avoiding the coverage of a large amount of coke on the Ni-Gd-Cr-O active center, effectively increasing the H2 yield and CO2 selectivity, and alleviating the deactivation problem of the catalyst caused by coke deposition; ② At the same time, the existence of these oxygen vacancy defects causes charge offset, resulting in uneven charge distribution in the Ni / GdCrO3 structure, changing the electron cloud density of Cr atoms, and promoting the 3+ / Cr 5+ transition between two valence states of Cr, thereby promoting the transfer of electrons to Ni 0 and making Ni 0The surrounding electron cloud density increases to form a rich charge state, which is beneficial to inhibit the active component Ni in the process of acetic acid autothermal reforming. 0 The oxidation of the active component Ni 0 agglomeration and sintering.
[0019] 3) The present invention constructs a new catalyst with a mesoporous structure. The mesoporous structure promotes the transfer and diffusion of reactants CH3COOH, H2O, O2 and product molecules H2, CO, CO2, while the confinement effect of the mesoporous structure confines Ni 0 Anchored on the carrier, it inhibits the aggregation of active components, improves the dispersion of the active component Ni in the GdCrO3 carrier, exposes more Ni-Gd-Cr-O active centers, and is beneficial to the breakage and dissociation of OH in the adsorbed CH3COOH (CH3COOH*→CH3COO*+H*).
[0020] 4) The catalyst of the present invention has high acetic acid conversion rate and high hydrogen yield during the acetic acid conversion process, and effectively inhibits carbon deposition, sintering and the active component Ni 0 oxidation, so the structure exhibits excellent catalytic performance: the acetic acid conversion rate is 100% and the hydrogen yield is 2.61 mol-H2 / mol-HAc. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 : X-ray diffraction spectrum of the catalyst of the present invention after calcination;
[0022] Figure 2 : BJH pore size distribution diagram of the catalyst of the present invention. DETAILED DESCRIPTION
[0023] Reference example one
[0024] Weigh 2.889g of Ni(NO3)2·6H2O and 6.625g of Cr(NO3)·9H2O, add appropriate amount of deionized water to prepare solution #1; weigh 7.236g of C6H8O7·H2O and 2.137g of (CH2OH)2, add appropriate amount of deionized water to prepare solution #2; mix solution #1 with solution #2, and stir continuously in a constant temperature water bath at about 70°C until a gel is formed; dry the gel in a vacuum drying oven at 105°C and foam for 12h; crush the dried and foamed sample, heat it to 700°C at a heating rate of 10°C / min, calcine for 4h, and reduce it in a H2 atmosphere for 1h to obtain a CDUT-NC catalyst with a molar composition of (NiO) a (CrO 1.5 ) bThe catalyst has a weight percentage composition of 37.1% nickel oxide and 62.9% chromium oxide in terms of oxides.
[0025] The activity evaluation of acetic acid autothermal reforming reaction was carried out in a continuous flow fixed bed reactor. The catalyst was ground and tableted, and after crushing, 20-40 mesh particles were screened out, loaded into the reactor, and reduced in a H2 atmosphere at 700°C and a flow rate of 30 mL / min for 1 hour. Then, the acetic acid-water mixed solution was injected into a vaporizer by a high-pressure constant flow pump for vaporization, and then mixed with oxygen after vaporization, and nitrogen was used as an internal standard gas to form a reaction raw gas with a molar composition of CH3COOH / H2O / O2=1 / (1.3-5.0) / (0.21-0.35), and this raw gas was passed into the catalyst bed for acetic acid autothermal reforming reaction. The reaction conditions were 500-800°C, normal pressure, and a space velocity of 20000-60000 mL / (g-catalyst·h). The reaction was analyzed online by a gas chromatograph.
[0026] The catalyst CDUT-NC was tested for its activity in autothermal reforming of acetic acid. Under the reaction conditions of normal pressure, space velocity of 30000 mL / (g-catalyst·h), reaction temperature of 700°C, raw gas acetic acid / water / oxygen = 1 / 4.0 / 0.28, reaction time of 10h, hydrogen yield was 1.97 mol-H2 / mol-HAc, the degree of reduction of the active component nickel was low, and partial sintering and carbon deposition occurred, indicating low activity.
[0027] Embodiment 1
[0028] Weigh 2.343g of Ni(NO3)2·6H2O, 5.963g of Gd(NO3)3·6H2O and 5.286g of Cr(NO3)·9H2O, add 35mL of deionized water to prepare solution #1; weigh 7.245g of C6H8O7·H2O and 2.140g of (CH2OH)2, add 176mL of deionized water to prepare solution #2; the subsequent steps are the same as those in reference example 1. After calcination at 700°C for 4h, its typical structure is as shown in the attached figure. Figure 1 As shown in FIG. 1 , a crystalline structure of NiO supported on a gadolinium chromite-type GdCrO3 oxide is formed, and a Ni-Gd-Cr-O active center is formed, thereby obtaining the gadolinium chromite-type nickel-based catalyst Ni / GdCrO3 of the present invention, i.e., CDUT-NGC catalyst; the catalyst is a mesoporous material, and its typical pore size distribution is shown in FIG. Figure 2 As shown; the catalyst molar composition is (NiO) a (GdO 1.5 ) b (CrO 1.5 ) cThe weight percentage composition of the oxides is: 15.0% nickel oxide, 59.9% gadolinium oxide, and 25.1% chromium oxide.
[0029] The activity of the CDUT-NGC catalyst was investigated by the autothermal reforming reaction of acetic acid. Under the reaction conditions of normal pressure, space velocity of 30000mL / (g-catalyst·h), reaction temperature of 700°C, feed ratio of CH3COOH / H2O / O2=1 / 4.0 / 0.28, and reaction time of 10h, the catalyst acetic acid conversion rate was close to 100%, hydrogen yield was 2.61mol-H2 / mol-HAc, CO2 selectivity was about 66%, CO selectivity was about 34%, and CH4 and acetone selectivity were close to 0; the overall activity of the catalyst was relatively stable during the test. The CDUT-NGC catalyst was characterized by BET, and the results were: the specific surface area was 11.2m 2 / g, pore volume is 0.1cm 3 / g, the average pore size is 17.8nm, and the most probable pore size distribution is 2.9nm. The characterization results show that the catalyst has no sintering, can effectively inhibit the production of by-products such as methane and acetone, and has the characteristics of high catalytic activity and stable hydrogen yield.
Claims
1. Application of gadolinium chromite type GdCrO3 nickel-based catalyst in the process of hydrogen production by autothermal reforming of acetic acid, characterized in that: The gadolinium chromite type GdCrO3 nickel-based catalyst is reduced in H2 at a temperature of 600-800°C for 1h, then purged with nitrogen, and a mixed gas with a molar ratio of acetic acid / water / oxygen = 1 / (1.3-5.0) / (0.21-0.35) is introduced through the catalyst bed to perform an autothermal reforming reaction at a reaction temperature of 600-800°C. The catalyst is prepared by the following method: a certain amount of nickel nitrate, gadolinium nitrate and chromium nitrate are weighed and dissolved in deionized water to prepare a mixed solution #1; a citric acid and ethylene glycol mixed solution #2 is prepared according to a total molar ratio of citric acid:ethylene glycol:metal nitrate of 1:1:1; solution # 1 was mixed with solution #2 and stirred, and the water bath was kept heated at 70°C, and stirring was continued until gel appeared, and the gel was moved to an oven at a temperature of 105°C for 12 hours, and the sample was foamed and expanded; the obtained sample was crushed and placed in a tube furnace for roasting, and the temperature was raised from room temperature to 600-800°C at a heating rate of 10°C / min, and the roasting was maintained for 4 hours to form a crystalline phase structure of NiO loaded on gadolinium chromite type GdCrO3 oxide, and a Ni-Gd-Cr-O active center was formed, thereby obtaining the gadolinium chromite type nickel-based catalyst Ni / GdCrO3 of the present invention; the molar composition of the catalyst in terms of oxide is (NiO) a (GdO 1.5 ) b (CrO 1.5 ) c , wherein a is 0.77-0.89, b is 1.13-1.40, and c is 1.12-1.57; the weight percentage composition calculated as oxides is: nickel oxide is 11.0%-15.5%, gadolinium oxide is 54.3%-65.9%, chromium oxide is 21.7%-32.2%, and the sum of the weight percentage composition of each component is 100%.
2. The use of the gadolinium chromite type GdCrO3 nickel-based catalyst according to claim 1 in the process of producing hydrogen through autothermal reforming of acetic acid, characterized in that: The catalyst has a weight percentage composition of 15.0% nickel oxide, 59.9% gadolinium oxide and 25.1% chromium oxide in terms of oxides.